2006
DOI: 10.1590/s0101-81752006000400032
|View full text |Cite
|
Sign up to set email alerts
|

Aves de um fragmento de Mata Atlântica no alto Rio Doce, Minas Gerais: colonização e extinção

Abstract: Foi conduzido um levantamento de espécies de aves em um fragmento florestal no alto Rio Doce de abril de 2002 a novembro de 2004. A região está inserida numa das áreas prioritárias para conservação da biodiversidade do Brasil, a Mata Atlântica. O fragmento está dentro da 'Estação de Pesquisa e Desenvolvimento Ambiental de Peti' (EPDA-Peti) e cerca uma represa de uma usina hidroelétrica das 'Companhia Energética de Minas Gerais'. O fragmento possui 605 ha de mata secundária semidecídua em vários estágios de reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
(2 reference statements)
1
8
0
7
Order By: Relevance
“…The bird fauna of Anchieta Island appears severely reduced when compared to adjacent mainland and forest fragments (GOERCK 1997, RIBON et al 2003, FARIA et al 2006), but it is in accordance to what has been found for other land-bridge islands in the Atlantic forest. The species abundances patterns may be quite different from the mainland because the community is dominated by a few hyperabundant species (RØV 1975,WIENS 1989.…”
Section: Discussionsupporting
confidence: 84%
“…The bird fauna of Anchieta Island appears severely reduced when compared to adjacent mainland and forest fragments (GOERCK 1997, RIBON et al 2003, FARIA et al 2006), but it is in accordance to what has been found for other land-bridge islands in the Atlantic forest. The species abundances patterns may be quite different from the mainland because the community is dominated by a few hyperabundant species (RØV 1975,WIENS 1989.…”
Section: Discussionsupporting
confidence: 84%
“…Three species of army ants ( Eciton burchelli, Eciton vagans , and Labidus praedator ) have been reported and 231 species of birds identified at our study site (Faria et al 2006). Mist‐netting and visual censuses of forest understory birds indicated that the most abundant birds in the area were White‐shouldered Fire‐eyes ( Pyriglena leucoptera ), White‐throated Spadebills ( Platyrhincus mystaceus ), and White‐bellied Warblers ( Basileuterus hypoleucus ; Faria et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that the area harbors approximately 29 species of anurans (Bertoluci et al, 2009), 231 species of birds (Faria et al, 2006) and 46 species of mammals (Paglia et al, 2005). A large part of the reserve is covered by secondary arboreal vegetation of continuous canopy and large trees (Nunes and Pedralli, 1995).…”
Section: Study Areamentioning
confidence: 99%